MODERN APPROACHES TO THE PREVENTION AND TREATMENT OF PREECLAMPSIA DURING PREGNANCY (World Bulletin of Public Health, 2024)
Preeclampsia is a hypertensive disorder of pregnancy with severe complications for both maternal and fetal health. Despite being a major cause of maternal and neonatal morbidity, effective strategies for early detection, prevention, and treatment remain critical. This article reviews the latest approaches to managing preeclampsia, focusing on evidence-based prevention strategies such as low-dose aspirin, lifestyle modifications, and nutritional interventions. Moreover, it highlights recent advancements in diagnostic biomarkers and emerging therapies like targeted gene therapies and anti-sFlt-1 treatments. The analysis emphasizes multidisciplinary approaches to improve maternal and neonatal outcomes worldwide.
Keywords: Preeclampsia; pregnancy; hypertension; maternal health